2018
DOI: 10.1177/0022034518769827
|View full text |Cite
|
Sign up to set email alerts
|

FGF2 Enhances Odontoblast Differentiation by αSMA+ Progenitors In Vivo

Abstract: The goal of this study was to examine the effects of early and limited exposure of perivascular cells expressing α (αSMA) to fibroblast growth factor 2 (FGF2) in vivo. We performed in vivo fate mapping by inducible Cre-loxP and experimental pulp injury in molars to induce reparative dentinogenesis. Our results demonstrate that early delivery of exogenous FGF2 to exposed pulp led to proliferative expansion of αSMA-tdTomato cells and their accelerated differentiation into odontoblasts. In vivo lineage-tracing ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…This mouse model was previously shown to target an amplifying osteoprogenitor population within the growing metaphysis . In addition, it labels quiescent adult progenitors within periosteum, epitenon, skeletal muscle, and dental pulp that activate in response to injury. Unlike growing bone, fewer quiescent mesenchymal progenitors within the adult bone marrow express αSMA compared with the periosteum, therefore there is minimal contribution of these cells to intramembranous bone formation within the medullary cavity following injury .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mouse model was previously shown to target an amplifying osteoprogenitor population within the growing metaphysis . In addition, it labels quiescent adult progenitors within periosteum, epitenon, skeletal muscle, and dental pulp that activate in response to injury. Unlike growing bone, fewer quiescent mesenchymal progenitors within the adult bone marrow express αSMA compared with the periosteum, therefore there is minimal contribution of these cells to intramembranous bone formation within the medullary cavity following injury .…”
Section: Discussionmentioning
confidence: 99%
“…This model labels a resident multipotent progenitor within the bone marrow that gives rise to new bone and adipocytes during growth and development. It also labels quiescent progenitor populations in the periosteum, paratenon, skeletal muscle, and dental pulp that activate in response to injury. In addition, αSMA is highly expressed by these cell populations during the early proliferative phase of the repair response.…”
Section: Introductionmentioning
confidence: 99%
“…[176] Recently, it was reported that early delivery of exogenous FGF2 to dental pulp resulted in accelerated odontoblast differentiation. [177] Integrated regeneration of tooth tissue requires the creation of an angiogenic network for the transfer of nutrients and oxygen between cells and the removal of by-products. It has been shown that amplification of the Wnt signaling pathway leads to the vascularization of human dental pulp stem cells.…”
Section: Delivery Of Growth Factorsmentioning
confidence: 99%
“…In another report, FGF-2 regulated and supported osteoblastic niche cells during hematopoietic homeostasis recovery after bone marrow suppression (17). The stimulatory effects of FGF-2 signaling were seen on odontoblast differentiation from early progenitors in dental pulp (18). There has been efficient generation of neurons from human bone marrow derived mesenchymal stem cells using FGF-2 alone (19).…”
Section: Discussionmentioning
confidence: 99%